1989
DOI: 10.1007/bf01739809
|View full text |Cite
|
Sign up to set email alerts
|

A model of crossbridge action: the effects of ATP, ADP and Pi

Abstract: We have explored a model of crossbridge kinetics that explains many of the effects on steady-state muscle contraction of ligands that bind to the nucleotide site on myosin. The mathematical model follows the basic framework for crossbridge function first established by A. F. Huxley. In the model, detached crossbridges initially bind in a weakly attached, A.M.D.Pi state (A, actin; M, myosin; D, ADP; Pi, orthophosphate) at the beginning of the region of positive force production. Pi release then results in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
235
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(262 citation statements)
references
References 54 publications
25
235
2
Order By: Relevance
“…They found that skeletal muscle myosin ATPase action was far less susceptible to ADP inhibition than either cardiac or smooth muscle myosin, and calculated that the approximate K i value (measured as competitive inhibition by ADP with respect to ATP) of skeletal muscle actomyosin was an order of magnitude greater than that of cardiac or smooth muscle. It is widely felt that the free [ADP] in skeletal muscle in vivo is insufficiently high to cause myosin ATPase inhibition [45]. Conversely, in cardiac muscle, ventilation under mild hypoxia (8ÏȘ10% O 2 ) can cause [ADP] to increase into the range where significant ATPase inhibition has been observed to occur in vitro [44].…”
Section: Discussionmentioning
confidence: 99%
“…They found that skeletal muscle myosin ATPase action was far less susceptible to ADP inhibition than either cardiac or smooth muscle myosin, and calculated that the approximate K i value (measured as competitive inhibition by ADP with respect to ATP) of skeletal muscle actomyosin was an order of magnitude greater than that of cardiac or smooth muscle. It is widely felt that the free [ADP] in skeletal muscle in vivo is insufficiently high to cause myosin ATPase inhibition [45]. Conversely, in cardiac muscle, ventilation under mild hypoxia (8ÏȘ10% O 2 ) can cause [ADP] to increase into the range where significant ATPase inhibition has been observed to occur in vitro [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that venous occlusion limited removal of metabolic products from the exercising ECR muscle. Among metabolic products, H+ and Pi are known to cause fatigue [8,27,29]. Furthermore, increase in H+ ion concentration has been demonstrated to produce a larger force reduction in the type IIb fibers compared to type I fibers [XI, and the ECR muscle is predominantly composed of type IIb fibers [I?].…”
Section: Discussionmentioning
confidence: 99%
“…First, at low ATP concentrations an increase in inorganic phosphate (P i ) to 50 mM caused a significant decrease in unloaded shortening velocity (20). Second, when fiber stiffness of isometrically contracting fibers was measured at different speeds of stretch, the stiffness-speed relations recorded in the presence of 5-10 mM P i were shifted to slower stretch velocities (21).…”
Section: In Addition Phosphate Did Not Extend Dwell Times Of Cy3-edamentioning
confidence: 99%